LNI-Adcal Auto Parts Sdn. Bhd. a Case Study - Lim, Yoke Khian (1997)
This case was about an automotive parts manufacturing company which experienced some difficulties in sustaining profitability i n its business operation. It had struggled through the early years to establish its name in the local automotive industry. The struggle was thought to be over when the turnover achieved the highest level in 1996. However, it was not so because the profitability had declined significantly. The price competition in the industry was intense particularly so in the OEM market. The problems were traced back to the annual price reduction exercises conducted by local automotive assemblers. Every year, the price reduction exercise was becoming severe and realised it has some difficulties in maintaining its competitiveness in the industry. The management believed that one of the solutions was to increase sales and at the same time, produced quality products which could lead to improved profit margins. Hence, there ought to be continuous improvement in the quality of the products through efficient use of the production facilities. As in the past years, the company did experience some quality problems in production and these incidences were gradually minimised with the introduction of quality measures and the replacement with new machines and equipment. Higher sales could be achieved through market expansion in domestic and regional markets. The management of LNI-Adcal Auto Parts has the first taste of export to the Philippines. Finally, the company hoped that through export, it could achieve the desired profitability and increased turnover.